Effect of intravenous lipid therapy in critically ill pediatric patients with calcium channel blocker toxicity - Yavuz, Sinan; Avcı, Ali; Gündoğan Serin, Rabia; Kaya, Mustafa Mesut; Ağalıoğlu, Dilfuza (The Turkish Journal of Pediatrics, 2024)
Background. Overdose with calcium-channel blockers (CCBs) still maintain their importance with a high lethality rate after exposure. We report the intravenous lipid emulsion therapy (ILE) therapy in our CCB overdose patients.Methods. We retrospectively analyzed the records of 6 patients with CCB intoxication from Batman Training and Research Hospital PICU between March 2021 and September 2022. Patients aged 0-18 years who received ILE treatment for CCB poisoning were included.Results. All six patients ingested CCB with the intention of committing suicide and were followed up in the pediatric intensive care unit (PICU). All patients received ILE therapy due to hemodynamic instability despite intravenous fluid boluses, calcium, glucagon, insulin-dextrose, and vasoactive agents. Vasoactive-Inotropic Score (VIS) decreased after ILE treatment. All patients were transferred from the PICU after recovery.Conclusions. ILE therapy should be kept in mind as a salvage therapy in hemodynamically unstable CCB poisoning cases that do not respond to initial and advanced options.
Keywords: calcium channel blockers; lipid emulsion; pediatrics; intoxication